The Influence of Work Ethic, Compensation and Employee Morale on Organizational Commitment at Company: Pengaruh Etos Kerja, Kompensasi dan Semangat Kerja Karyawan Terhadap Komitmen Organisasi di Perusahaan - Nasir, M. Ali Amin; Andriani, Dewi (Indonesian Journal of Law and Economics Review, 2022)
In the era of globalization, the existence of an agency or organization is very dependent on the performance of the human resources who work in it. Implementation of organizational commitment in human resource management is needed in order to maintain membership in the organization. The research approach used is a descriptive quantitative approach. The survey method is carried out by distributing questionnaires to a number of respondents to examine the correlation of several variables on the hypothesis that has been made. The population of this research is all employees of PT Mutiara Masyhur Sejahtera, totaling 70 people. In this study, linear regression analysis was chosen as a data analysis technique using SPSS version 16. The results showed that work ethic had a positive and significant effect on organizational commitment, compensation had a positive and significant effect on organizational commitment, work morale had a positive and significant effect on organizational commitment. . So that the work ethic, compensation, and work spirit have a simultaneous effect on organizational commitment at PT Mutiara Masyhur Sejahtera